2017
DOI: 10.1007/s10578-017-0736-x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Clarity, Anxiety Sensitivity, and PTSD Symptoms Among Trauma-Exposed Inpatient Adolescents

Abstract: Although several investigations-on primarily adult samples-demonstrate a potential role of emotion dysregulation in the etiology and maintenance of posttraumatic stress disorder (PTSD), investigations into the mechanisms that may underlie these associations in general and among adolescents in particular are lacking. The present study examined associations among emotional clarity (i.e., the extent to which individuals are confused about the specific emotions they are experiencing), (Gratz, Journal of Psychopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In line with our hypothesis, we found that elevated emotion dysregulation at baseline predicted increases in PTSS at Month‐1 follow‐up through heightened AS at Week 3, after controlling for treatment condition and initial PTSS and AS. These findings are consistent with limited cross‐sectional work examining the mechanistic role of AS as it relates to emotion dysregulation and PTSS (Viana et al, 2018; Viana et al, 2017; Woodward et al, 2018), and expands this work by utilizing a diverse clinical sample of adults. Theory suggests that emotion dysregulation may entail greater difficulties discerning between bodily sensations and negative emotional states, leading individuals to view bodily sensations as unpredictable and frightening (Tull, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with our hypothesis, we found that elevated emotion dysregulation at baseline predicted increases in PTSS at Month‐1 follow‐up through heightened AS at Week 3, after controlling for treatment condition and initial PTSS and AS. These findings are consistent with limited cross‐sectional work examining the mechanistic role of AS as it relates to emotion dysregulation and PTSS (Viana et al, 2018; Viana et al, 2017; Woodward et al, 2018), and expands this work by utilizing a diverse clinical sample of adults. Theory suggests that emotion dysregulation may entail greater difficulties discerning between bodily sensations and negative emotional states, leading individuals to view bodily sensations as unpredictable and frightening (Tull, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties engaging in goal‐oriented behaviors when distressed may restrict exposure to situations involving high anxious arousal; in turn, individuals may not learn corrective information about internal sensations that may accompany PTSD hyperarousal (Tull & Gratz, 2008). While our results are the first to demonstrate the significance of this subscale within the proposed mediational model, these findings are inconsistent with recent cross‐sectional work highlighting the roles of emotional clarity and nonacceptance (Viana et al, 2018; Viana et al, 2017). It may be that global emotion dysregulation exhibits a larger effect size and may be most useful to consider for predicting PTSS through AS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have empirically demonstrated that difficulties in each stage of the emotion regulation process following traumatic events may contribute to the development of PTSD. For example, when emotional clarity is low, the negative impact of traumatic events was significantly greater (Shipman et al, 2005;Viana et al, 2018). Another study showed that implementing maladaptive emotion regulation strategies (e.g., emotional avoidance) as a response to emotional difficulties can lead to PTSD (Tull et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety is a very common behavioral disorder associated with a traumatic experience in humans [1][2][3][4] . The use of animal models to describe brain disorders related with traumatic events represents an important tool for development of new treatments and drug discoveries.…”
mentioning
confidence: 99%